(untitled) (The Review of Diabetic Studies, 2025)
This paper focused on evaluate the clinical outcomes, perioperative parameters, in addition to risk factors associated with Glenn circulation failure in patients with single ventricle congenital heart disease (CHD). Where our method as defined, A retrospective observational analysis was conducted on 80 patients with single ventricle physiology who underwent Glenn palliation between 2018 and 2023. Demographic, clinical, perioperative, and postoperative data were collected from medical records. Notably, Key variables included age, weight, preoperative oxygen saturation, congenital anomaly subtype, prior palliation history, perioperative hemodynamics, and postoperative complications. Logistic regression analysis identified independent predictors of Glenn circulation failure.